Respostas
respondido por:
3
x² + 5x + 6= 0
Δ= -b² -4 .a .c
Δ= -5² -4 .1 . 6
Δ= 25 - 24
Δ= 1
x' = -b - √Δ/ 2.a
x' = -5 - 1/ 2.1
x'=-6/2 = -3
x"= -b + √Δ/ 2.a
x"= -5 + 1/ 2.1
x" -4/2 = -2
Δ= -b² -4 .a .c
Δ= -5² -4 .1 . 6
Δ= 25 - 24
Δ= 1
x' = -b - √Δ/ 2.a
x' = -5 - 1/ 2.1
x'=-6/2 = -3
x"= -b + √Δ/ 2.a
x"= -5 + 1/ 2.1
x" -4/2 = -2
respondido por:
2
X² + 5x + 6 = 0
a = 1
b = 5
c = 6
Δ = b² -4 .a . c
Δ = 5² - 4 . 1 . 6
Δ = 25 - 4 . 6
Δ = 25 - 24
Δ = 1
Resposta: S{-2 , -3}
a = 1
b = 5
c = 6
Δ = b² -4 .a . c
Δ = 5² - 4 . 1 . 6
Δ = 25 - 4 . 6
Δ = 25 - 24
Δ = 1
Resposta: S{-2 , -3}
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás